(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research the used descriptive method of the TPR method to teach vocabulary to students at SMA Negeri 12 Sinjai. The purpose of this research was determined whether the TPR method effectived for teaching vocabulary. The method used was qualitative method. This research selected participants from students of SMAN 12 Sinjai for the academic year 2021/2022. The sample consisted of 24 students, 11 students from X IPA 3 and 13 students from XI IPA 1. This research used two kinds of instruments, namely observation and interviews. The results of this research found that the use of the TPR method could help students to improve their vocabulary. Most students of SMAN 12 Sinjai like learning by using the TPR method, TPR also helps students increase vocabulary and pronounce fluently. On the other hand, this strategy was effective in teaching students to know new vocabulary in class. Based on the observations, there were several students who had problems such as 12 students having problems with self-confidence, 10 students having problems with pronunciation, and based on the results of interviews 20 of 24 students agreed that the TPR method could improve vocabulary.